Swarm Intelligence 10th International Conference, ANTS 2016, Brussels, Belgium, September 7-9, 2016, Proceedings - Dorigo, Marco; Birattari, Mauro; Li, Xiaodong; López-Ibáñez, Manuel; Ohkura, Kazuhiro; Pinciroli, Carlo; Stützle, Thomas (Theoretical Computer Science and General Issues, 2016)
This book constitutes the proceedings of the 10th International Conference on Swarm Intelligence, ANTS 2016, held in Brussels, Belgium, in September 2016. The 18 full papers and 7 short papers presented in this volume were carefully reviewed and selected from 47 submissions. They are devoted to the field of swarm intelligence as a whole, without any bias towards specific research directions. .